2015
DOI: 10.1523/jneurosci.3914-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

How Visual Is the Visual Cortex? Comparing Connectional and Functional Fingerprints between Congenitally Blind and Sighted Individuals

Abstract: Classical animal visual deprivation studies and human neuroimaging studies have shown that visual experience plays a critical role in shaping the functionality and connectivity of the visual cortex. Interestingly, recent studies have additionally reported circumscribed regions in the visual cortex in which functional selectivity was remarkably similar in individuals with and without visual experience. Here, by directly comparing resting-state and task-based fMRI data in congenitally blind and sighted human sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
68
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 72 publications
10
68
4
Order By: Relevance
“…reported that when blind subjects and sighted subjects listened to the names of large objects such as "couch" or "refrigerator" in contrast to small tools and animals, the PHG was significantly more strongly activated, and this activation overlapped well with the parahippocampal place area (Epstein and Kanwisher, 1998;Epstein, 2008). These findings were replicated in the study by Wang et al (2015) and are consistent with the findings in the study by Wolbers et al (2011), who reported that in both blind and sighted subjects, haptic exploration of Lego scenes elicited stronger activation in the PHG than did the exploration of Lego objects. We thus used the selectivity for large objects in PHG as a test case for the effect of visual experience in the mapping between white matter connectivity and regional functional preferences.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…reported that when blind subjects and sighted subjects listened to the names of large objects such as "couch" or "refrigerator" in contrast to small tools and animals, the PHG was significantly more strongly activated, and this activation overlapped well with the parahippocampal place area (Epstein and Kanwisher, 1998;Epstein, 2008). These findings were replicated in the study by Wang et al (2015) and are consistent with the findings in the study by Wolbers et al (2011), who reported that in both blind and sighted subjects, haptic exploration of Lego scenes elicited stronger activation in the PHG than did the exploration of Lego objects. We thus used the selectivity for large objects in PHG as a test case for the effect of visual experience in the mapping between white matter connectivity and regional functional preferences.…”
Section: Introductionsupporting
confidence: 91%
“…For example, the same subjects may produce different functional response profiles in a particular brain region when performing different tasks. In the current context, Wang et al (2015) showed that sighted subjects had different category response profiles in posterior lateral fusiform and inferior occipital gyrus when viewing pictures and when listening to names, indicating that different tasks can recruit different sets of connections within an identical white matter background.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These include the anterior intraparietal area [involved, among other tasks, in producing accurate grip (41)(42)(43)] and the ventral premotor cortex (44)(45)(46). Furthermore, the fact that similar tool-selective and body-selective responses have been found in the same part of the occipito-temporal cortex in individuals deprived of visual experience from birth (32,33,47,48), invites the inference that, because vision is not necessary for developing theses preferences, the burden for shaping this region's functional specialization is carried by motor experience. Our finding, however, calls for a reexamination of this experience-based account.…”
Section: Discussionmentioning
confidence: 99%
“…Still, to account for the topographic arrangement of the hand and tool specialization, we would need to assume that the region in question is preferentially disposed to encode information about those object categories independently of a specific type of sensory input. This would, in turn, suggest that the nature of representations in this region would need to be of a form that is accessible through different modalities, including written words (48), haptic stimulation (49,50), or sensory-substitution-based audition (51), and that they be independent from low-level effectorbound motor properties and experience, such that they develop normally in individuals with atypical bodies, as in the dysplasics.…”
Section: Discussionmentioning
confidence: 99%